Answer:
(a)3√13 Units
(b)
![((5√(5))/(2),-2√(2))](https://img.qammunity.org/2023/formulas/mathematics/college/65dwvm2tudyn7085ot8xuf2wxxzfnf7m1f.png)
Step-by-step explanation:
Part A
We determine the distance between the two points using the distance formula.
![\text{Distance}=√((x_2-x_1)^2+(y_2-y_1)^2)](https://img.qammunity.org/2023/formulas/mathematics/college/ry4ih03dlg8wxpauy6sz70wqq5qg0w0gq9.png)
Therefore, the distance between points (√5, √2) and (4√5, -5√2) is:
![\begin{gathered} =\sqrt{(4√(5)-√(5))^2+(-5√(2)-√(2))^2} \\ =\sqrt{(3√(5))^2+(-6√(2))^2} \\ =√((3^2*5)+((-6)^2*2)) \\ =√(45+72) \\ =√(117) \\ =3√(13)\text{ Units} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xximkawrydzg1d4lz73dugp0euz055ry0u.png)
The exact distance between the points is 3√13 Units.
Part B
We determine the midpoint of the line segment whose endpoints are the given points using the midpoint formula.
![\text{Midpoint}=((x_1+x_2)/(2),(y_1+y_2)/(2))](https://img.qammunity.org/2023/formulas/mathematics/college/5r4htz68x8ojrwv6fukh4dehd0pq6ujr7b.png)
Therefore:
![\begin{gathered} \text{Midpoint}=((√(5)+4√(5))/(2),(√(2)+(-5√(2)))/(2)) \\ =((5√(5))/(2),(-4√(2)))/(2)) \\ =((5√(5))/(2),-2√(2)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ln9y6cx0xey5u5g6w9m7hagp7yrttlt05u.png)